CONSTRUCTING THE WITCH: A DISCOURSE ANALYSIS OF IDENTITY AND SPIRITUALITY IN THE WITCH OF PORTOBELLO USING JAMES PAUL GEE’S SEVEN BUILDING TASKS OF LANGUAGE - Wiguna, Riefki Fajar Ganda; Felayati, Safrina Arifiani (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2025)
This paper examines Paulo Coelho’s The Witch of Portobello through the lens of Critical Discourse Analysis (CDA), using James Paul Gee’s Seven Building Tasks of Language as the central analytical framework. Through the narrative of Athena, a woman whose spiritual journey defies societal conventions, the novel offers a rich ground for exploring how language constructs identity, power, and belief systems. By integrating Gee’s model with Norman Fairclough’s socio-cultural approach and Teun A. van Dijk’s socio-cognitive perspective, this study demonstrates how language functions as a tool for ideological subversion and identity formation in literary texts. This analysis finds that Coelho utilizes language not only to tell a story but also to contest dominant narratives of gender, spirituality, and authority.